Rehabilitation of shoulder instability in junior hanbalists a challenge for physiotherapists - Dorobăț Simona Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
This study's relevance stems from the high incidence of injuries among junior handball athletes, particularly instability injuries, which necessitate prolonged recovery periods and extended absences from the team. Forty handball playeres included in the study (LE=20 and LC=20). Both groups underwent initial evaluations regarding pain induced by the injury, daily activity, mobility, and strength. We analyzed the functional balance and had participants complete questionnaires to assess activity limitations due to shoulder injuries and instability, as well as functional impairment. After completing the recuperative program, the control group followed a traditional rehabilitation program, while the experimental group followed the proposed program. LE made important progress analyzed to the LC in terms of functional impairment due to pain and recovery from disability caused by instability injuries, according to post-evaluation results.